Análise de série temporal da hanseníase no estado do Pará - PINHEIRO, Helder Henrique Costa (Universidade Federal do Pará, 2017)
Objective: Analysing a time series of new cases detected of Leprosy in the State of Pará, checking epidemiological trends according to the observated variables of the disease. Methods: Ecological observational design of detection historical series of Leprosy cases with use of secondary data from the National Notifiable Diseases System. The detection rates and the general variables in studies and estimated the trends of the time series were calculated. The State of Pará data were compared to the States of Mato Grosso State and Rio Grande do Sul. Results: The detection rate in Pará in 2014 was 4,84 per 10.000 inhabitants, with 32.177 cases detected in the period 2008-2014, estimating a trend annual growth rate of -12.71%. The proportion of children under 15 years of age was 10.4%, the largest in Brazil. Higher frequency of MB cases (65,2%) and Borderline clinical form (45,2%) was deteceted. Conclusion: The detection of new cases of leprosy is mainly in adult men, poorly educated and living in urban areas. The downward trend in case detection of the disease is different from stationary trend in the State of Mato Grosso. However, the trend of leprosy cases in children and adolescents in the State of Pará is stationary.